IO4−‐stimulated crosslinking of catechol‐conjugated hydroxyethyl chitosan as a tissue adhesive. Issue 3 (7th May 2018) - Peng, Xiaoting; Peng, Yanfei; Han, Baoqin; Liu, Wanshun; Zhang, Fuming; Linhardt, Robert J
Abstract: Catechol‐functionalized polymers are of particular interest because of their strong water‐resistant adhesive properties. Hydroxymethyl chitosan (HECTS) has been used as an implantable biomaterial having good water solubility, biodegradability and biocompatibility. Here, hydrocaffeic acid (HCA) grafted HECTS (HCA‐ g ‐HECTS) was prepared through carbodiimide coupling and the tethered catechol underwent periodate ( IO 4 − )‐stimulated mono and double cross‐linking with genipin. The gelation time of these cross‐linked HCA‐ g ‐HECTS hydrogels decreased with increasing molar ratio of cross‐linker to grafted catechol group, increasing temperature, or the addition of genipin. Under the same molar ratio of cross‐linker to catechol, IO 4 − ‐induced cross‐linked HCA‐ g ‐HECTS hydrogels exhibited much stronger storage modulus and temperature stability than hydrogels made by Fe 3+ ‐triggered cross‐linking. The IO 4 − ‐stimulated HCA‐ g ‐HECTS hydrogels were biocompatible on a cellular level when the molar ratio of IO 4 − to catechol group was less than 0.5:1. The hydrogels prepared with a 0.125:1 molar ratio of IO 4 − to catechol group exhibited high adhesion strength of 73.56 kPa against wet rat skin, and a higher adhesion strength than sutures in a rat wound closure model. This biocompatible IO 4 − ‐stimulated HCA‐ g ‐HECTS hydrogel may represent a promising new tissue adhesive. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2018. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 582–593, 2019.